Green Synthesis: An Eco-friendly Route for the Synthesis of Iron Oxide Nanoparticles - Priya,; Naveen,; Kaur, Kamaljit; Sidhu, Amanpreet K. (Frontiers in Nanotechnology, 2021)
Green approach has received major attention for the synthesis of metallic nanoparticles. One such metallic nanoparticles are iron oxide nanoparticles (IONPs). IONPs have fetched a great deal of interest in recent era because of their magnetic nature, as they can be easily recovered from the reaction mixture by applying an external magnetic field.Although, a variety of chemical and physical methods of synthesis are known, green synthesis is safer, sustainable and biologically acceptable. Plants and microbes are the main biological materials used for the green biosynthesis. In present review, the synthesis of IONPs by using plants, bacteria, fungi and algae have been highlighted. IONPs produced by plants, fungi, bacteria and algae usually falls in 1-200nm range and are of distinct shapes like cubic, tetragonal crystalline, spherical, cylindrical, elliptical, octahedral, orthorhombic, hexagonal rods, nanosphere and quasi spherical. Furthermore, these biomaterials play role of reducing, capping, stabilizing and fabricating agents in biosynthesis of nanoparticles. The review put forward a comprehensive report of various routes used for synthesizing IONP, biologically.Intuition into the procedures for synthesis of nanoparticles will help to nourish our learning in the area of nanotechnology.